Molecular Characterization and Phylogenetic Analysis of Enterocytozoon bieneusi in Lambs in Oromia Special Zone, Central Ethiopia - Wegayehu, Teklu; Li, Junqiang; Karim, Md. Robiul; Zhang, Longxian (Frontiers in Veterinary Science, 2020)
Enterocytozoon bieneusi is the most frequently diagnosed microsporidian species in humans and occurs in a wide range of animals. This study was conducted in Central Ethiopia to determine the prevalence and genotypes of E. bieneusi in lambs in order to evaluate their public health significance. Three hundred eighty nine fecal samples were collected and screened using a nested PCR targeting the internal transcribed spacer (ITS) of the ribosomal RNA gene. All positive PCR products were sequenced to determine the genotypes. E. bieneusi was found in 39 (10.03%) of the lambs. Differences in the infection rates among sex and age groups were not significant (P > 0.05). Five ITS genotypes belonging to three known genotypes BEB6, COS-I and COS-II, and two novel genotypes (ET-L1 and ET-L2) were identified in lambs. All five genotypes identified in the present study clustered within cattle-specific Group 2 in the ITS phylogenetic tree. This first molecular detection and characterization of E. bieneusi in lambs in Ethiopia has identified the need for further studies in humans and other domestic animals in order to determine the public health significance of E. bieneusi in Ethiopia.